1998
DOI: 10.1177/002221949803100201
|View full text |Cite
|
Sign up to set email alerts
|

Selective Predictive Value of Rapid Automatized Naming in Poor Readers

Abstract: This study considers the differential predictive value of rapid naming tests for various aspects of later reading, where the differential is between nondisabled and poor readers. Two large-N longitudinal samples of students who have been evaluated from third through eighth grades are studied: (a) a randomly accessed, normally distributed group including students with varying degrees of reading ability (N = 154), and (b) a group of poor readers whose single-word reading in third grade is at or below the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
130
3
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(165 citation statements)
references
References 29 publications
20
130
3
12
Order By: Relevance
“…This is similar to the findings of Pennington et al (2001), who found that naming speed in a cross-sectional sample did not contribute significantly to measures of reading when reading and vocabulary were controlled. In contrast, Meyer, Wood, Hart, and Felton (1998) found that in a longitudinal study with 64 children with dyslexia and a random control sample of 154 students, third-grade naming speed had predictive power for single-word reading in fifth and eighth grade for poor readers (classified as below 10th percentile on word recognition) but not for average readers.…”
Section: The Nature Of the Relationship Between Naming Speed And Readmentioning
confidence: 81%
“…This is similar to the findings of Pennington et al (2001), who found that naming speed in a cross-sectional sample did not contribute significantly to measures of reading when reading and vocabulary were controlled. In contrast, Meyer, Wood, Hart, and Felton (1998) found that in a longitudinal study with 64 children with dyslexia and a random control sample of 154 students, third-grade naming speed had predictive power for single-word reading in fifth and eighth grade for poor readers (classified as below 10th percentile on word recognition) but not for average readers.…”
Section: The Nature Of the Relationship Between Naming Speed And Readmentioning
confidence: 81%
“…However, with greater exposure and practice in relation to letters and numbers, the naming of alphanumeric stimuli becomes more automatic. At this point, the alphanumeric stimuli are named faster and become more strongly associated with the ability of reading 29 . These differences highlight the importance of considering the alphanumeric stimuli RAN separately from non-alphanumeric stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Neste âmbito, tem-se destacado que a nomeação rápida: se correlaciona significativamente com a leitura (por ex., Bowers & Swanson, 1991;Manis et al, 2000;Savage et al, 2005;Wolf et al, 2002); explica variância do desempenho em leitura depois de se ter controlado a influência de outras variáveis relevantes, como a consciência fonológica, isto é, exerce uma influência específica no desenvolvimento das competências de leitura (Cutting & Denckla, 2001;Manis et al, 2000;Manis, Seidenberg, & Doi, 1999); e prediz o desempenho subsequente em leitura (Meyer, Wood, Hart, & Felton, 1998;van den Bos, Zijlstra, & Spelberg, 2002;Wolf et al, 1986). Nota-se, no entanto, que o poder preditivo da nomeação rápida é influenciado por diversas variáveis, sendo, por exemplo, mais importante em crianças mais jovens (Torgesen, Wagner, Rashotte, Burgess, & Hecht, 1997;Wolf et al, 1986), em crianças com dificuldades de aprendizagem (Lepola, Poskiparta, Laakkonen, & Niemi, 2005;Meyer et al, 1998) e em ortografias transparentes (Landerl, 2001;Lepola et al, 2005;van den Bos, 1998).…”
unclassified